Advances in nanomaterials for treatment of hypoxic tumor. Issue 2 (8th July 2020) - Zou, Mei-Zhen; Liu, Wen-Long; Chen, Han-Shi; Bai, Xue-Feng; Gao, Fan; Ye, Jing-Jie; Cheng, Han; Zhang, Xian-Zheng
Abstract: The hypoxic tumor microenvironment is characterized by disordered vasculature and rapid proliferation of tumors, resulting from tumor invasion, progression and metastasis. The hypoxic conditions restrict efficiency of tumor therapies, such as chemotherapy, radiotherapy, phototherapy and immunotherapy, leading to serious results of tumor recurrence and high mortality. Recently, research has concentrated on developing functional nanomaterials to treat hypoxic tumors. In this review, we categorize such nanomaterials into (i) nanomaterials that elevate oxygen levels in tumors for enhanced oxygen-dependent tumor therapy and (ii) nanomaterials with diminished oxygen dependence for hypoxic tumor therapy. To elevate oxygen levels in tumors, oxygen-carrying nanomaterials, oxygen-generating nanomaterials and oxygen-economizing nanomaterials can be used. To diminish oxygen dependence of nanomaterials for hypoxic tumor therapy, therapeutic gas-generating nanomaterials and radical-generating nanomaterials can be used. The biocompatibility and therapeutic efficacy of these nanomaterials are discussed.